2014
DOI: 10.5455/medarh.2014.68.254-258
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Clinical, Radiographic and Functional Scores on the Total Score in the Evaluation of Congenital Clubfoot

Abstract: Introduction:The use of radical surgical treatments in treating congenital clubfoot is decreasing. Minimally invasive surgical treatment (MIST) is a way of treating congenital clubfoot, which is a kind of compromise between a radical surgical treatment and non-operational one. A few protocols of different authors McKay, Macnicol, Stevens, Meyer, G.W.Simons and Laaveg-Ponseti were used in the evaluation of the results. SCIENTIFIC OBJECTIVE: To determine the importance and role of groups of parameters (clinical,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Unless a limb deficiency such as fibular hemimelia, tibial hemimelia, or congenital short femur is noted, radiography is not necessary. 25 Several syndromes are known to be associated with clubfoot, including classic arthrogryposis, multiple pterygium syndrome, distal arthrogryposis, amniotic band syndrome, and Freeman-Sheldon syndrome. [26][27][28] Geneticists can help to evaluate patients when there is suspicion of a syndrome.…”
Section: Newborn Evaluationmentioning
confidence: 99%
“…Unless a limb deficiency such as fibular hemimelia, tibial hemimelia, or congenital short femur is noted, radiography is not necessary. 25 Several syndromes are known to be associated with clubfoot, including classic arthrogryposis, multiple pterygium syndrome, distal arthrogryposis, amniotic band syndrome, and Freeman-Sheldon syndrome. [26][27][28] Geneticists can help to evaluate patients when there is suspicion of a syndrome.…”
Section: Newborn Evaluationmentioning
confidence: 99%
“…Prasad et al [12] studied the correlation between clinical scores and 12 radiological parameters in 30 patients (50 feet) with CTEV who were treated with posteromedial soft tissue release (PMSTR) and they concluded that all the radiological parameters were showing good correlation with clinical parameters. In a study by Rakonjac et al [13] in 48 children (84 feet), radiological score (TaCA in both AP and lateral views, TFM in AP view, TiCA in lateral view, TCI) was correlated against clinical score (Pirani score) in children undergoing radical surgery (group A) and minimally invasive surgery (group B) and proved that there was a significant positive correlation between clinical and radiological score. Similar results were observed in studies done by several other investigators where all the considered radiological parameters had significant correlation with clinical scores [14].…”
Section: Discussionmentioning
confidence: 94%
“…In a study by Rakonjac et al . [13] in 48 children (84 feet), radiological score (TaCA in both AP and lateral views, TFM in AP view, TiCA in lateral view, TCI) was correlated against clinical score (Pirani score) in children undergoing radical surgery (group A) and minimally invasive surgery (group B) and proved that there was a significant positive correlation between clinical and radiological score.…”
Section: Discussionmentioning
confidence: 96%